3+2z=5z-3-3z+6

Simple and best practice solution for 3+2z=5z-3-3z+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+2z=5z-3-3z+6 equation:


Simplifying
3 + 2z = 5z + -3 + -3z + 6

Reorder the terms:
3 + 2z = -3 + 6 + 5z + -3z

Combine like terms: -3 + 6 = 3
3 + 2z = 3 + 5z + -3z

Combine like terms: 5z + -3z = 2z
3 + 2z = 3 + 2z

Add '-3' to each side of the equation.
3 + -3 + 2z = 3 + -3 + 2z

Combine like terms: 3 + -3 = 0
0 + 2z = 3 + -3 + 2z
2z = 3 + -3 + 2z

Combine like terms: 3 + -3 = 0
2z = 0 + 2z
2z = 2z

Add '-2z' to each side of the equation.
2z + -2z = 2z + -2z

Combine like terms: 2z + -2z = 0
0 = 2z + -2z

Combine like terms: 2z + -2z = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4c-19=17 | | -4c-9.6+5c=o | | -75+9x-x=9 | | 4-i(3b-8)=2b-17 | | 8x-3x+2=x-9+11 | | 2q^2+2q+24=0 | | 2b+3b=-10 | | 70+11x+11=180 | | (3x/4)-(1/3)=1-(2/3)-(1/6) | | 70+11x=180 | | 8x-x+2=x-9+11 | | 0x-4=6 | | 4y+5=4y+2 | | 20a-2a+32=12a-6 | | 5x+10/5=-4 | | 3=m/14+4 | | 2x+3x-4=10x+6 | | F/4-5=-9 | | 4p+10=4p-2 | | (3+5x)/5=(4-x)/8 | | 3x+5=ax+5 | | 3.5+17=2.75+12+.5X | | -2+2=5y-1 | | 5b-4=3b+5 | | -4x+10=3x+9 | | -6y-70y=-32 | | 7x-7=-x-1 | | 9x^4-18x^2-x+14=0 | | (5x-2)-(6-2x)=x-9+5x | | -4x-8x+17=23 | | 4(2x-7)=128 | | 2-(3/4)z=(1/8)z+9 |

Equations solver categories